S-1 maintenance therapy in Caucasian patients with metastatic esophagogastric adenocarcinoma: final results of the randomized AIO MATEO phase II trial - Stocker, Gertraud; Lorenzen, Sylvie; Ettrich, Thomas J.; Herz, Anne-Lina; Longo, Federico; Kiani, Alexander; Venerito, Marino; Trojan, Jörg; Mahlberg, Rolf; Moosmann, Nicolas; Chibaudel, Benoist; Kubicka, Stefan; et al. (ESMO open, 2023)
Purpose - Platinum-fluoropyrimidine combinations are standard of care for treatment of metastatic esophagogastric adenocarcinoma. The optimal duration of first-line chemotherapy is unknown, however, and maintenance strategies have not yet been established. - Design - MATEO is an international randomized phase II trial exploring efficacy and safety of S-1 maintenance therapy in human epidermal growth factor receptor 2 (HER2)-negative advanced esophagogastric adenocarcinoma. After 3 months of first-line platinum-fluoropyrimidine-based induction therapy, patients without progression were randomized in a 2 : 1 allocation to receive S-1 monotherapy (arm A) or to continue combination chemotherapy (arm B). The primary objective was to show non-inferiority of overall survival in the S-1 maintenance group. Progression-free survival, adverse events, and quality of life were secondary endpoints. - Results - From 2014 to 2019, 110 and 55 patients were randomized in arm A and arm B, respectively (recruitment closed prematurely). Median overall survival from randomization was 13.4 months for arm A and 11.4 months for arm B [hazard ratio 0.97 (80% confidence interval 0.76-1.23), P = 0.86]. Median progression-free survival from randomization was 4.3 and 6.1 months for arm A versus arm B, respectively [hazard ratio 1.10 (80% confidence interval 0.86-1.39), P = 0.62]. Patients in arm A had numerically fewer treatment-related adverse events (84.9% versus 93.9%) and significantly less peripheral sensory polyneuropathy ≥grade 2 (9.4% versus 36.7%). - Conclusions - S-1 maintenance following platinum-based induction therapy leads to non-inferior survival outcomes compared with the continuation of platinum-based combination. Toxicity patterns favor a fluoropyrimidine maintenance strategy. These data challenge the continued use of platinum combination chemotherapy after response to 3 months induction therapy in patients with advanced human epidermal growth factor receptor 2-negative esophagogastric adenocarcinoma.
Interim results of this trial have been presented at ESMO Congress 2020 and DGHO Congress 2020
Gesehen am 06.10.2023